The Nonlinear Boundary Value Problems of Three Elements for the First Order Quasilinear Elliptic Systems (Journal of Partial Differential Equations, 1992)
In this paper, we discuss the nonlinear boundary value problems of three elements with two shifts for the first order quasilinear elliptic systems and the related solvability by using the continuity method.
Keywords: The first order quasilinear elliptic systems; nonlinear boundary value problems; continuity method